Shape comparison of eyes by ellipse fitting technique / Nor Azmuha Azreen Johari - Johari, Nor Azmuha Azreen (2010)
This prototype is developed to detect the shape comparison of eyes using Ellipse Fitting. This study is focus on ancestry which the comparison process is done within children and parent from same ancestry and also does the comparison within different ancestry to look the differences result. Sometimes the data from digital camera produce poor data which contain a lot of noise compare to image take in studio. Noise image can be removed with several combination of method. Good quality of image is done and used in comparison process which Ellipse Fitting technique is applied to detect the shape circle of eyes and Manhanttan Distance is used to find the lowest distance result between child and father and also between child and mother. This application is also can be used in forensic agency, medical and security.